2005
DOI: 10.1111/j.1469-0691.2004.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida and antibiotic-associated diarrhoea

Abstract: The role of Candida in antibiotic-associated diarrhoea (AAD) has been controversial for many years. Since Candida exists physiologically in the gastrointestinal tract, the presence of small numbers of Candida organisms in stool has therefore been considered normal, and thus non-pathogenic. Increased Candida counts have been linked to the development of diarrhoea in antibiotic-treated patients. However, recent findings have not confirmed this. To date, there is no convincing evidence that Candida may cause AAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…This led to worsening of DSS-induced colitis and exacerbated allergic airway disease [52]. Conversely, another study found patients receiving antibiotics, resulting in antibiotic-associated diarrhoea (AAD), had disturbance to the indigenous microbiota preceding Candida overgrowth in the GI tract (reviewed in [53]). Candida species and Geotrichum candidum have been implicated in causation of IBS in patients who had received prior anti-bacterials, as these patients seemed to respond to nystatin, an anti-fungal preparation [54,55].…”
Section: The Gut Mycobiome and Disease Susceptibilitymentioning
confidence: 99%
“…This led to worsening of DSS-induced colitis and exacerbated allergic airway disease [52]. Conversely, another study found patients receiving antibiotics, resulting in antibiotic-associated diarrhoea (AAD), had disturbance to the indigenous microbiota preceding Candida overgrowth in the GI tract (reviewed in [53]). Candida species and Geotrichum candidum have been implicated in causation of IBS in patients who had received prior anti-bacterials, as these patients seemed to respond to nystatin, an anti-fungal preparation [54,55].…”
Section: The Gut Mycobiome and Disease Susceptibilitymentioning
confidence: 99%
“…The effect of broad‐spectrum antibiotics on the intestinal microbiota is characterised by the decrease in protective bacterial populations and the increase in fungi. However, the role of fungi in AAD is still controversial . It has been reported that the faecal concentrations of Candida sp.…”
Section: Role Of Fungi In Pathogenesis Of Gi Disordersmentioning
confidence: 99%
“…However, the role of fungi in AAD is still controversial. 15,164 It has been reported that the faecal concentrations of Candida sp. of ≥10 5 CFU/mL can cause diarrhoea in patients receiving antibiotic therapy, but which <10 5 CFU/mL do not.…”
Section: Role Of Fungi In Aadmentioning
confidence: 99%
“…C. albicans ist bis zur abschließenden Klärung dieser Frage daher eher als Kommensale denn als opportunistischer Keim zu bezeichnen. In einzelnen Studien konnte allerdings eine Besserung der Durchfallsymptomatik nach Gabe von Antimykotika gezeigt werden [1,16].…”
Section: Eine Antibiotikaassoziierte Diarrhö (Aad) Kann Bei Bis Zu 25unclassified